Phase II study of capecitabine (Ro 09-1978) in patients who have failed first line treatment for locally advanced and/or metastatic cervical cancer - Vicharn Lorvidhaya (2018)
Purpose: The objective of this study is to evaluate the efficacy and safety of capecitabine in cervical cancer patients who have locoregional failure and/or distant metastasis and failed first line therapy. The efficacy of capecitabine is determined by the overall response rate (ORR) according to WHO criteria for response and the safety by adverse event (AE) and tolerability profiles according to NCI CTC version 2. 0. Patients and Methods: Patients with loco-regional failure and/or metastatic cervical cancer who have failed first line therapy were enrolled into the study. The patient received capecitabine 1, 250 mg/m2 twice daily for 14 consecutive days with 7 days rest (21-day cycle). The treatment was continued for up to six cycles. Results: Forty-five patients previously treated by single or combination of surgery, or chemotherapy or radiotherapy were enrolled for study. Thirty-seven of 45 patients (82%) received at least 2 cycles of treatment and they were evaluated for response. The intention to treat analyses revealed 6/45 (13%) ORR, 1/45 (2%) CR and 5/45 (11%) PR. Twenty-four patients (53%) had stable disease and 20% had progression of the disease. The median time to progression was 4. 1 months and the median overall survival was 9. 3 months. Conclusion: Capecitabine as a monotherapy has a modest response in locoregional failure and/or metastatic cervical cancer who have failed first line therapy.